Geology of Setap Shale Formation, Sarawak - Sector 3 - Abu Bakar, Nurin Firzanah (2016)
The study of Geology of Setap Shale formation is aiming on observing the potential of shale gas in the Setap shale formation. The main objectives are to produce a geological map and to identify the properties of shale from Setap Formation including both physical and chemical properties at the outcrop located on street sideways of Jalan Beluru-Bakong (E3’ 59’’, N114’ 02’’).